(untitled) (Bangladesh Journal of Zoology, 2010)
The fecundity of Macrognathus pancalus was measured by Gravimetric method and fecundity was found to range from 866.93±117.65 to 2074.25±88.79 from 100 samples having a total length from 47.90±1.27 to 83.19±1.71 mm, body weight from 5.71±0.37 to 30.74±1.62 g and gonad weight from 3.56±0.44 to 5.06±0.48 g. A screening test of different doses of common hormonal substance pituitary gland (PG) from 5.0 mg to 185.0 mg/kg body weight and 5.0 mg to 60.0 mg/kg body weight were tested for different length of time to find out the accurate dose which responses the ovulation and spermiation of M. pancalus. A double dose of PG extracts (2.0 mg and 180.0±1.01 mg/kg body weight) was the best effective dose in ovulation and a single dose of PG (60.0±1.05 mg/kg body weight) was most effectual in spermiation. Bangladesh J. Zool. 38(1): 77-91, 2010